The Lived Experiences of Gym Rats in Pursuit of their Ideal Physique - Hibanada, Paula Faye; Dee, Pinky; Limosnero , Rolando; Baje, Zyril Kaiser; Ignacio, Darwin (Journal of Interdisciplinary Perspectives, 2025)
Gym rats are dedicated to enhancing their physique and overall health. As they are motivated by various inspirations, they also face challenges that may hinder their progress. To explore their lived experiences in pursuing an ideal physique, this study aimed to investigate the motivations, challenges, and coping strategies they employ through a qualitative phenomenological approach. Semi-structured, face-to-face interviews were conducted among 10 participants, using purposive sampling. Furthermore, the data collected were analyzed using Braun and Clarke’s (2006) thematic analysis method. Results revealed that gym rats pursue fitness for reasons like self-image, health, social influence, and peer conformity. However, they also face challenges that hinder their fitness journey, such as financial constraints, time management issues, daily responsibilities, and intrapersonal conflicts. The study further revealed the coping strategies gym rats use to overcome these challenges, including time management, adapting to circumstances, building a support network, and reinforcing their drives. From the collected data, the researchers concluded that gym rats are driven to pursue an ideal physique by specific motivating factors. Despite these motivations, they still encounter obstacles that often hinder their progress and may decrease their workout motivation. Nevertheless, gym rats actively combat these challenges through coping strategies that help them stay on track and committed to their fitness goals. The findings of this study may serve as a foundation for gaining insights into developing interventions to address these challenges, ultimately supporting gym rats in their pursuit of an ideal physique.